Immediate Postnatal Microbial Colonization in Sick Term Neonates Admitted to NICU: Prevalence, Microbiota, and Associated Characteristics - Verma, Rita P.; Kota, Archana; Fogel, Joshua (American Journal of Perinatology, 2021)
Objective The immediate postnatal rectal (RC) and nasopharyngeal colonization (NPC), their prevalence, taxa, and associated characteristics were investigated in sick term infants admitted to the neonatal intensive care unit.Study Design In a retrospective cohort single center study, nasopharyngeal (NPCx) and rectal (RCx) microbial cultures were obtained within 20 minutes of birth in mild-to- moderate sick term infants. Associations between the colonization and maternal–neonatal variables, including early neonatal course, were analyzed via logistic regression analysis.Results A total of 154 term infants were admitted for respiratory distress, hypoglycemia, maternal chorioamnionitis (CHO), and suspected neonatal sepsis; out of which, 80 (52%) were NPCx-positive (+) infants. The duration of rupture of membrane (ROM) was higher (15.5 ± 10.0 vs. 11.3 ± 11.0 hours, p = 0.02), while the respiratory support requirement (16.3 vs. 29.7%, p = 0.04) and occurrence of maternal group B Streptococcus (GBS) colonization lower (15.0 vs. 35.1%, p = 0.01) in NPCx+ infants. ROM increased (odds ratio [OR]: 1.04, 95% confidence interval [CI]: 1.01–1.07), and maternal GBS colonization decreased the odds of positive nasopharyngeal cultures (OR: 0.31, 95% CI: 0.14–0.72). The major microorganisms isolated were Staphylococcus epidermidis (41%), α hemolytic Streptococcus (AHS; 16%), Escherichia coli (13%), and GBS (1.06%). Among the enrolled infants, 44 (28.5%) were RCx positive. The need for (11.4 vs. 27.3%, p = 0.03) and days on respiratory support (0.2 ± 0.6 vs. 0.8 ± 2.5, p = 0.03) were lower and the occurrence of CHO higher (41.0 vs. 23.2%, p = 0.04) in the RCx positive infants. Cesarean section (CS) was performed less frequently (18.2 vs. 55.5%, p = 0.001) and decreased the odds of having positive rectal cultures (OR: 0.21, 95% CI: 0.08–0.51). In total, 80% of the RCx positive infants isolated E. coli, and 6.8% Klebsiella.Conclusion In sick term neonates, early NPC is dominated by SE and RC by E. coli. NPC is supported by ROM and declines by maternal GBS colonization, whereas RC decreases with CS. NPC is more common than RC in this population.Key Points
Keywords: nasopharyngeal microbial colonization; rectal microbial colonization; term neonates; respiratory morbidities; chorioamnionitis; cesarean section